Tax consequences of the 2010 FIFA World Cup - Olckers, Teresa (Department of Commercial Law, 2015)
With all the excitement in South Africa about the 2010 FIFA World Cup kicking off on 11 June 2010, tax relief will be granted on import tax and VAT, amongst others, in terms of the Revenue Laws Amendment Act 20 of 2006 (hereafter referred to as RLAA). FIFA (Federation Internationale de Football Association), confirmed that SAFA may have the right to serve as a host for the 2010 FIFA World Cup, but in order to qualify 17 guarantees were to be given by South African government to FIFA which is a general requirement for all host cities. These guarantees will be provided by various government departments focusing on the financial environment, safety and security, intellectual property and marketing rights, transport and telecommunications as well as custom duties, other taxes and duties and levies by the Minister of Finance. The government of The Republic of South Africa issued several guarantees that they would comply with to meet certain requirements set out by FIFA for World Cup hosts (Wilson, 2008:1). These include, inter alia, the provision of taxation relief for qualifying individuals and entities. Trevor Manuel, former Minister of Finance, included certain provisions in the RLAA, to give effect to FIFA’s requirements. The RLAA created a tax-free bubble around the FIFA-designated sites so that profits on consumable and semi-durable goods sold within these areas will not be subject to Income tax; nor will VAT be levied. Tax relief will be given on specific goods and services for qualifying taxpayers, as defined in the Income Tax Act 58/1962 ("The Income Tax Act"), (Wilson, 2008:1). This relief system will be governed by an accompanying abuse paragraph in the legislation in order to limit any loss that may be suffered by the South African Revenue Service ("SARS"). The positive and negative impacts, which will arise from hosting such an international event, are important to discuss and consider.